Agroecological principles and elements and their implications for transitioning to sustainable food systems. A review - Wezel, Alexander; Herren, Barbara Gemmill; Kerr, Rachel Bezner; Barrios, Edmundo; Gonçalves, André Luiz Rodrigues; Sinclair, Fergus (Agronomy for sustainable development, 2020)
There is consensus that the global food system is not delivering good nutrition for all and is causing environmental degradation and loss of biodiversity, such that a profound transformation is needed to meet the challenges of persistent malnutrition and rural poverty, aggravated by the growing consequences of climate change. Agroecological approaches have gained prominence in scientific, agricultural and political discourse in recent years, suggesting pathways to transform agricultural and food systems that address these issues. Here we present an extensive literature review of concepts, definitions and principles of agroecology, and their historical evolution, considering the three manifestations of agroecology as a science, a set of practices and a social movement; and relate them to the recent dialogue establishing a set of ten iconic elements of agroecology that have emerged from a global multi-stakeholder consultation and synthesis process. Based on this, a consolidated list of principles is developed and discussed in the context of presenting transition pathways to more sustainable food systems. The major outcomes of this paper are as follows. (1) Definition of 13 consolidated agroecological principles: recycling; input reduction; soil health; animal health; biodiversity; synergy; economic diversification; co-creation of knowledge; social values and diets; fairness; connectivity; land and natural resource governance; participation. (2) Confirmation that these principles are well aligned and complementary to the 10 elements of agroecology developed by FAO but articulate requirements of soil and animal health more explicitly and distinguish between biodiversity and economic diversification. (3) Clarification that application of these generic principles can generate diverse pathways for incremental and transformational change towards more sustainable farming and food systems. (4) Identification of four key entry points associated with the elements: diversity; circular and solidarity economy; co-creation and sharing of knowledge; and, responsible governance to enable plausible pathways of transformative change towards sustainable agriculture and food systems.